2019
DOI: 10.1007/s11095-019-2634-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Plasma Membrane Localization and Phosphorylation Status of Organic Anion Transporting Polypeptide (OATP) 1B1 c.521 T>C Nonsynonymous Single-Nucleotide Polymorphism

Abstract: Purpose: Membrane transport protein organic anion transporting polypeptide (OATP) 1B1 mediates hepatic uptake of many drugs (e.g. statins). The OATP1B1 c.521T>C (p. V174A) polymorphism has reduced transport activity. Conflicting in vitro results exist regarding whether V174A-OATP1B1 has reduced plasma membrane localization; no such data has been reported in physiologically relevant human liver tissue. Other potential changes, such as phosphorylation, of the V174A-OATP1B1 protein have not been explored. Current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 72 publications
3
28
1
Order By: Relevance
“…Similar as shown in Figure 2, using DNA (50 ng) from biopsy FFPE tissues in a 20 μl volume also yielded successful amplification of the 339 bp PCR product (data not shown). Sequencing of the expected 339 bp PCR products from different tissues was able to distinguish between all three genotypes, c. 521 TT, TC and CC (Figure 3 and also as shown in the original publication [Crowe et al , 2019]). The FFPE tissues from both surgical resection and biopsy specimens are all suitable for genotyping using the current method.…”
Section: [Background]supporting
confidence: 55%
See 1 more Smart Citation
“…Similar as shown in Figure 2, using DNA (50 ng) from biopsy FFPE tissues in a 20 μl volume also yielded successful amplification of the 339 bp PCR product (data not shown). Sequencing of the expected 339 bp PCR products from different tissues was able to distinguish between all three genotypes, c. 521 TT, TC and CC (Figure 3 and also as shown in the original publication [Crowe et al , 2019]). The FFPE tissues from both surgical resection and biopsy specimens are all suitable for genotyping using the current method.…”
Section: [Background]supporting
confidence: 55%
“…Also, this method optimized the amount of template DNA from FFPE tissue suitable for PCR. This protocol is reproducible and requires a small amount of tissue, even from biopsy specimens, to yield sufficient PCR products for Sanger-sequencing-based genotyping of OATP1B1 c. 521 T>C. This method has also been successfully used for genotyping of another polymorphism of OATP1B1 c. 388 A>G (Crowe et al , 2019).…”
Section: [Background]mentioning
confidence: 99%
“…The early investigations reported that the p.174Val>Ala variation was associated with a decreased membrane localization and a decreased Vmax value with no change in Km value (111,112). A recent study, however, reported different findings that the Val174Ala variation does not necessarily reduce the OATP1B1 level at the plasma membrane (113). Instead, the authors noted that Val174Ala variation is associated with a modest increase in protein phosphorylation.…”
Section: Oatp1b1mentioning
confidence: 99%
“…Therefore, these results suggested that SNPs in SLCO genes may also alter the transport functionality of the OATPs. For example, a nonsynonymous SNP in OATP1B1 was previously identified to change its phosphorylation status, subcellular localization, and the ability to transport its substrate estradiol glucuronide (49).…”
Section: Discussionmentioning
confidence: 99%